Uruk: first city of the ancient world - Crüsemann, Nicola; Ess, Margarete van; Hilgert, Markus; Salje, Beate; Potts, Timothy F. (The J. Paul Getty Museum, 2019)
This remarkable book unveils the origins of urban life in our ancient past. Over one hundred years ago, discoveries from a German archaeological dig at Uruk, roughly two hundred miles south of present-day Baghdad, sent shock waves through the scholarly world. Founded at the end of the fifth millennium BC, Uruk was the main force for urbanization in what has come to be called the Uruk period (4000-3200 BC), during which small, agricultural villages gradually gave way to a larger urban center with a stratified society, complex governmental bureaucracy, and monumental architecture and art. It was here that we find, circa 3400 BC, protocuneiform script-the earliest known form of writing. One of the most fascinating Mesopotamian sites ever discovered, Uruk is also known for the epic tale of its hero-king Gilgamesh, among the earliest masterpieces of world literature. This abundantly illustrated volume offers the most comprehensive and up-to-date assessment of the archaeological evidence gathered in excavations at Uruk over the past century. More than sixty essays by renowned scholars provide glimpses into the life, culture, and art of the first great city of the ancient world.0This volume will be indispensable to both specialists and general readers interested in the origins of urbanism